Ofrenda : Liliana Wilson's Art of Dissidence and Dreams - Cantú, Norma E., 1947-; Cantú, Norma E., 1947-; Wilson, Liliana, 1953- (Book collections on Project MUSE., 2014)
Liliana Wilson's art of resistance and protest, dissidence and dreams, consistently calls attention to injustice. Wilson belongs to a group of Chilean artists who were intimately shaped by the political turmoil and repression in Chile in the 1970s and 1980s and who have become self-exiled artists working outside of Chile but who are still tied to the political period and to its issues and concerns. From a working class family that struggled financially, Wilson nonetheless was able to study law, which facilitated her successful immigration to the United States in 1977. She moved to Texas and in.